If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = 7x + -12 Reorder the terms: -4 + 9x = 7x + -12 Reorder the terms: -4 + 9x = -12 + 7x Solving -4 + 9x = -12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -4 + 9x + -7x = -12 + 7x + -7x Combine like terms: 9x + -7x = 2x -4 + 2x = -12 + 7x + -7x Combine like terms: 7x + -7x = 0 -4 + 2x = -12 + 0 -4 + 2x = -12 Add '4' to each side of the equation. -4 + 4 + 2x = -12 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = -12 + 4 2x = -12 + 4 Combine like terms: -12 + 4 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 8x+9y=970 | | 4=2x-18 | | 14-h=16 | | -5n+8=73 | | -4+2(r-10)=9-(r-9) | | -7-x-2x=-22 | | 35=(2x-3)x | | 21-8x=53 | | 5y+x^2=x+6 | | 7p+5p=-3(p+10)+3(p-10) | | 10x-5x+8= | | 5(x-10)=40 | | 3y-8(8y-60)=53 | | 15(b+2)+15+2b-9+b=90 | | 7x-11=-6(1-5x)-5 | | 5x=3.304 | | 9(x-2)+2=-16 | | 2n-2=16 | | 8+-3x=x | | 1+x+3x=1 | | x+3y+2x+y=90 | | 9(1-k)+1=-(8k+6) | | 15-=-4m+5 | | 15x-1=9x | | x+x+9/3=2(3x-8)+9 | | log(x+4)=log(4x-2) | | x(4+2)=3(x-5) | | 9x(c+3-9)=13c+5x | | .6x+6=-.6x-6 | | 3(4x-2)-2(1-x)=-22 | | 3x^2+5xy-y^2=7 | | -3v-2v=0 |